Administration of Chemistry Programme in Nigerian Higher Institutions: Problems and way Forward - Izunna Somadina Okwelogu; Oladokun Benjamen Niran; Ogunode Niyi Jacob (Researchparks Publishing, 2021)
Chemistry programme is one of the programme offered in the Nigerian higher institutions. It is a programme that is science inclined and vital to the social economic and technological advancement of Nigeria. The article discussed the challenges facing the administration of Chemistry programme in the Nigerian higher institutions. Secondary data was used to support the points raised in the article. The secondary data were sourced from printed material and online publication by recognized institutions and individual author. The article identified the following: inadequate funding of chemistry programme, shortage of chemistry lecturers, inadequate infrastructural facilities, brain-drain, strike actions and poor staff training as the challenges facing the administration of chemistry programme in the Nigerian higher institutions. To solve these challenges, this article recommends the following: government should increase the funding of chemistry programme in higher institutions, provide adequate infrastructural facilities, ensure stable academic programme, employment of more chemistry lecturers and motivation of lecturers to prevent brain-drain.